(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the artistic expression of the teachings of Bahauddin Naqshband and the Naqshbandi order. The article expresses an opinion on the artistic expression of the ideas of the Naqshbandi order.